2007
DOI: 10.1002/nau.20442
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of early intensive prolonged pelvic floor exercises on urinary continence recovery after bladder neck‐sparing radical prostatectomy: Results of a prospective controlled randomized trial

Abstract: Our study suggests that early intensive prolonged PFE can further increase the number of continent patients and this improvement persists in the first 12 months. The second 6 months following surgery are still useful to recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
2
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 23 publications
7
87
2
9
Order By: Relevance
“…[61][62][63] In multivariate analyses of pre-and postoperative factors, significant factors that improved chances of postoperative continence were younger age, preservation of both neurovascular bundles, absence of an anastomotic stricture, preservation of functional urethral length, eversion of the bladder neck, and a smaller prostate volume. 61,[64][65][66][67][68] If incontinence is present, pelvic floor exercise, as well as biofeedback, may be beneficial.…”
Section: Urinary and Sexual Functionmentioning
confidence: 99%
“…[61][62][63] In multivariate analyses of pre-and postoperative factors, significant factors that improved chances of postoperative continence were younger age, preservation of both neurovascular bundles, absence of an anastomotic stricture, preservation of functional urethral length, eversion of the bladder neck, and a smaller prostate volume. 61,[64][65][66][67][68] If incontinence is present, pelvic floor exercise, as well as biofeedback, may be beneficial.…”
Section: Urinary and Sexual Functionmentioning
confidence: 99%
“…Die BP kann bei prostatogen bedingtem Nachtröpfeln [51,52], nach TUR-P [53] oder nach radikaler Prostatektomie [54] zur Verbesserung der Belastungsinkontinenz führen.…”
Section: Therapieoptionen Der Belastungsinkontinenz Beckenbodenphysiounclassified
“…There were several studies on the role of Pelvic Muscle Exercises (PME), Electrical Stimulation (ES), and biofeedback (BFB) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Of thesis studies, some showed better continence for PME group (3,(6)(7)(8)(9)(10)(11)(12)(13), while others did not show improvement (4,5,(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Of thesis studies, some showed better continence for PME group (3,(6)(7)(8)(9)(10)(11)(12)(13), while others did not show improvement (4,5,(14)(15)(16)(17)(18)(19)(20). ES is one method, which may enhance the success of PME in patients with incontinence after RP (12,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation